Asset pricing and housing supply in a production economy - Ivan Jaccard (European Central Bank (ECB), 2012)
We develop a representative agent model of a production economy in order to explain the joint dynamics of house prices and equity returns. In a model generating costly business cycle fluctuations, we find that restrictions on housing supply have important implications for asset pricing. Together with habit formation in the composite of consumption and leisure, building restrictions provide an explanation for the high volatility of house prices and contribute to the resolution of asset pricing puzzles.
Keywords: E2; E3; G1; 330; adjustment costs; cost of business cycle; House prices; housing returns